Historical Study of the System of Social Structure of Hadramaut Arab Descendants in Surakarta - Suryo Ediyono; Alif Al Hilal Ahmad; Muhammad Farkhan Mujahidin; Abdul Malik; Ahmad Jazuli (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
Research on historical studies on the social structure of the Hadramaut Arab descent community in Surakarta in the 21st century. The Hadramaut descent community grows and develops which has specific social stratification in their life that is continuous from the past, present, to the future. The study of the ancestry of the Hadramaut Arab community in Surakarta was initiated from their grandparents to being inherited by their great-grandchildren. The process of cultural adaptation and acculturation that they carry out has changed and has survived until now. The historical approach to this research is people of Arab descent using descriptive qualitative methods and interviews with Arabs in Surakarta. As a result, the people of Hadramaut descent have developed from the land of their birth and were brought down to the overseas lands where they live in Surakarta for generations. Starting from the Sayyid group, tribe, middle class, to helpers.